Quality of live pregnant women with hiv/aids : serial cases - Eka Yadnya, Ni Putu; Darmayasa, I Made (Andalas Obstetrics And Gynecology Journal, 2025)
Objective: HIV cases in women are often discovered because patients undergo antenatal screening examinations. Pregnant women with Human Immunodeficiency Virus (HIV) must have access to antiretroviral therapy (ART) as soon as possible and continuously. This protects the mother's health and prevents transmission of HIV to the fetus before birth or through breast milk. Pregnant women with HIV tend to have worse psychosocial impacts compared to non-pregnant patients, thus affecting their quality of life; Method: A qualitative research using a case report approach. Data on pregnant women with HIV was taken from secondary data, namely the cohort data of pregnant women at the Maternal and Child Health Polyclinic, I Melaya Health Center, Jembrana Regency between January 2022 to February 2024. Patients who were willing to take part in the research became respondents and were then interviewed using the WHOQOL-HIV-BRIEF instrument. Then a qualitative analysis of the results of the interviews conducted was carried out; Result:There are five case reports discussed, 80% or four cases had poor or even poor quality of life. Only 20% of cases have a good quality of life. The dominant aspects that influence thpatient's quality of life are the independence aspect in 80% of cases, the social, environmental and spiritual aspects in 40% of cases each. Meanwhile, the aspects that cause good quality of life values are physical and psychological aspects, each accounting for 80% of cases; Conclusion :There are several factors that can influence the good or bad quality of life of pregnant women with HIV. These include education level, income level, openness about HIV status, family support, adherence to treatment, individual coping mechanisms, and severity of HIV symptoms. It is very important to assess every pregnant woman with HIV/AIDS infection as an integral part of antenatal care. Keywords: Pregnant women; HIV ;quality of life